How community pharmacists perceive generic substitution impact on community pharmacies profits in absence of medicines price control policy: a Malaysian pilot nationwide study - Ahmad, Nor Amalina; Abd-Jabar, Nur-Hamizah; Awaluddin, Noor Hamizah; Kamaruddin, Nursyahirah; Mohd-Rasid, Nursyazwani; Elsayed, Tarek Mohamed Ali; Elkalmi, Ramadan Mohamed Mahmod; Hammad, Mohamed Anwar (SAGE Journals, 2017)
Background Generic medicines are introduced to the market after the expiry of the patented innovator medicine. Being usually sold at lower prices compared to branded medicines, they may provide a low-cost alternative for consumers. In Malaysia, where there is no Medicines Price Control Policy, it is not known if pharmacy profits differ between generic and branded medicines. It is also not known if this difference may affect pharmacists practice of generic substitution.